Lipid Profiles and Liver Functions Tests in Kidney Stone Formers - KAKEY, ISMAIL SALIHAL; KHAFAR, KANIAW RAFHAT (Science Journal of University of Zakho, 2013)
This study included 106 stone former patients (60 males with 46 females), who attended the Teaching Hospital in Sulaimani Governorate between April to June 2012. The diagnosis of the cases were done in the hospital, based on history, clinical examination followed by Kidney x-ray, ultrasonography, and urinalysis, also the study included 28 healthy (14 male with 14 female) person as control.The investigations included measurement of the liver function tests and renal functions tests beside the lipid profile in stone formers . Automatic chemical analyzer (Benchtop automatic biochemistry analyzer,ELITech) used for measuring total serum glucose , serum cholesterol, triglycerides (TG), cholesterol-HDL, serum LDL, serum VLDLserum albumin, alkaline phosphatase (ALP), Aspartate transferase (AST), Alanine aminotransferase (ALT), gamma glutamyltransferase (GGT), serum bilirubin and serum blirubin. The results demonstrated significant elevation in the levels of the serum cholesterol, triglyceride, LDL- cholesterol , VLDL- cholesterol, glucose, ALP, AST, GGT and LDH concentrations in renal stone former patients of both sex groups, with non significant lowering of the HDL- cholesterol in renal stone former patients.while albumin is lowered significantly with non significant differences in the serum ALT and bilirubin concentrations between renal stone former patients and controls groups. In conclusion, the results showed physiological relations of lipid metabolism and liver function with state of kidney dysfunction.